2015
DOI: 10.1186/s40663-015-0058-z
|View full text |Cite
|
Sign up to set email alerts
|

Wild foods (plants and animals) in the green famine belt of Ethiopia: Do they contribute to household resilience to seasonal food insecurity?

Abstract: Background: The role of wild foods in combating problems of food shortage is paramount. However, existing approaches to combat food insecurity shock have generally focused on reducing vulnerability via increasing productivity of domesticated foods. In contrast, approaches that enhance resilience mainly through wild food sources have been less focused. This study examined the contribution of wild foods to household resilience to food insecurity in the green famine belt of Ethiopia. Methods: A cross-sectional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Most of the available studies from various regions have found that socio-cultural factors are the main drivers of the reduced consumption of WEPs [ 70 , 71 ]. It has been strongly believed, mainly by indigenous peoples, that wild foods have a greater capacity to maintain the good health of those who depend on them [ 72 ]. Despite their accessibility and availability, the utilization of WEPs is challenged by numerous factors [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the available studies from various regions have found that socio-cultural factors are the main drivers of the reduced consumption of WEPs [ 70 , 71 ]. It has been strongly believed, mainly by indigenous peoples, that wild foods have a greater capacity to maintain the good health of those who depend on them [ 72 ]. Despite their accessibility and availability, the utilization of WEPs is challenged by numerous factors [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the result of Amenu [ 79 ] and Mesfin et al [ 80 ] indicated that roots are mostly used for medicinal and edible purposes. On the other hand, Guyu and Muluneh [ 81 ] reported that 52.4% of the total amount of wild foods came from wild vegetables, which is about 5 times higher than fruits and roots. The variation in consumption of wild edible plant parts might be due to the variation of plant species in adapting to different ecological zones and culture of the people in different areas.…”
Section: Contribution Of Wild Edible Plants To Food and Nutrition mentioning
confidence: 99%
“…There was a strong belief, mainly by the indigenous people, that wild foods have a greater capacity to maintain the good health conditions of those who depend on them [ 81 ]. Anbessa [ 76 ] indicated that the majority of wild edible plants were eaten as extra food rather than as regular meals.…”
Section: Attitudes Of Consumers To Wild Edible Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their environmental and economic functions such as timber, fuel wood, fodder, water and soil protection, carbon sequestration, oxygen production, recreation, aesthetics, biodiversity, and habitat for wildlife species are described in vast literature (Köchli &Brang 2005;Keleş et al 2008;Başkent et al 2008). Specially, their economic functions such as contribution to food security in general (Shriar, 2002) and being a major source of wild foods in particular are paramount (Guyu & Muluneh, 2015). However, forests of Ethiopia including Anbessa forest have experienced LULC changes due to mainly human activities (McKee, 2007;Mathewos, 2019).…”
Section: Introductionmentioning
confidence: 99%